Children explore to understand the physical world Research and practice in Early Childhood Education - Moeed, Azra; Saha, Sankari (Annals of Mathematics and Physics, 2022)
All children are inquisitive and begin to make sense of the physical and natural world around them from the time they are born. Children use their senses to explore the surrounding environment. Early Childhood Centres (ECE) in New Zealand provide care and learning opportunities for children under the age of 5-years. Te Whāriki, our mandated curriculum guides teachers. In an exploratory case study, we investigated the science learning experiences provided by an ECE teacher and the children’s learning that ensued. The data were collected through case study teacher interviews, mentor notes, and 160 learning stories written by the teacher during the research over two years. We found that a teacher with little background in science was able to provide rich science learning experiences for the children. The teacher’s willingness to provide everyday science exploration opportunities and ask questions helped children to develop basic physics concepts. Current research suggests that science is often not taught due to the lack of teacher confidence to teach science because they are generalists and believe they do not have the requisite knowledge or training. Our findings have implications for science teaching and learning in early childhood and primary schools.